2023
DOI: 10.3390/tropicalmed8010059
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Evolutionary Relationships within Neodermata Using Putative Orthologous Groups of Proteins, with Emphasis on Peptidases

Abstract: The phylogenetic relationships within Neodermata were examined based on putative orthologous groups of proteins (OGPs) from 11 species of Monogenea, Trematoda, and Cestoda. The dataset included OGPs from BUSCO and OMA. Additionally, peptidases were identified and evaluated as phylogenetic markers. Phylogenies were inferred using the maximum likelihood method. A network analysis and a hierarchical grouping analysis of the principal components (HCPC) of orthologous groups of peptidases were performed. The phylog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 92 publications
1
6
0
Order By: Relevance
“…In line with the latest phylogenetic analysis confirming a closer relationship of the monogenean subclass Polyopisthocotylea to trematodes than to cestodes [ 18 ], we observed that most E. nipponicum proteins are homologues (based on annotation in the UniProt/UniRef100 protein database) to monogenean representative Protopolystoma xenopodis ( n = 2,360), followed by trematodes, such as Paragonimus westermani ( n = 608), Schistosoma japonicum ( n = 462), Echinostoma caproni ( n = 429), and cestode Schistocephalus solidus ( n = 410) (Table 5 ).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In line with the latest phylogenetic analysis confirming a closer relationship of the monogenean subclass Polyopisthocotylea to trematodes than to cestodes [ 18 ], we observed that most E. nipponicum proteins are homologues (based on annotation in the UniProt/UniRef100 protein database) to monogenean representative Protopolystoma xenopodis ( n = 2,360), followed by trematodes, such as Paragonimus westermani ( n = 608), Schistosoma japonicum ( n = 462), Echinostoma caproni ( n = 429), and cestode Schistocephalus solidus ( n = 410) (Table 5 ).…”
Section: Resultssupporting
confidence: 82%
“…They perform essential functions in a broad range of physiological processes, such as protein metabolism, feeding, anticoagulation, digestion, regulation of development, immune evasion, and reproduction, and they have been intensively studied and repeatedly reviewed [ 74 77 ]. Moreover, peptidases can be used to reveal both micro- and macroevolutionary changes during the evolution of parasites [ 18 , 66 ]. Majority of identified individual peptidases ( n = 54) belong to peptidases with serine catalytic type, specifically to the S1 family (chymotrypsin family, PA clan) and S1A subfamily (chymotrypsin A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Schistosoma spp. because of the phylogenetic proximity among Trematoda, Cestoda and Polyopisthocotyla [ 1 , 2 ] and considering their genomic quality based on individual genome assembly statistics. The same steps and criteria as described above were employed to interrogate S. chrysophrii datasets for these neodermate homologues.…”
Section: Methodsmentioning
confidence: 99%
“…Monogeneans, recently reclassified into two unrelated classes, Monopisthocotyla and Polyopisthocotyla [ 1 , 2 ], are important aquatic, mainly ectoparasitic neodermates whose presence in fish farms pose a significant bottleneck for fish health, welfare, performance and economic revenue due to the artificial environment in which livestock is set [ 3 ].…”
Section: Introductionmentioning
confidence: 99%